Family Problems of Heart Patients and the Medical Social Worker’s Role facing them: A study applied to a sample of heart patients in Al-Madinah Al-Munawwarah Hospitals - Harmoush, Amna Ahmed Abdullah (Journal of Humanities & Social Sciences, 2024)
The study aimed to identify the family problems facing heart patients, determine the roles of the social worker in facing these problems, identify the obstacles that limit the role of the medical social worker in dealing with heart patients, and present a number of proposals that contribute to overcoming these obstacles. In terms of type, this study is a descriptive study, and the study relied on the use of the comprehensive social survey approach with social workers and the sample survey with heart patients. To collect the data, a questionnaire was used that the researcher designed to achieve the objectives of the study, The study population included all social workers in the hospitals under study, who numbered (80) social workers who responded to the questionnaire, number (67) of them, as well as patients in the same hospitals, and their number was (78) patients. The results showed that the members of the social workers sample agreed to some extent about the existence of family problems related to the patient’s heart pattern, and also agreed that the patient had family problems related to the family pattern, while members of the heart patients sample were neutral in their opinions about the presence of family problems facing the patient. the heart, The same was true of family problems related to the patient’s family. Among the most prominent obstacles facing social workers in performing their role with heart patients: is the medical team’s lack of awareness of the importance of the social worker’s role with them in treatment.